2020
DOI: 10.1080/10717544.2020.1775725
|View full text |Cite|
|
Sign up to set email alerts
|

Self-assembled dihydroartemisinin nanoparticles as a platform for cervical cancer chemotherapy

Abstract: Dihydroartemisinin (DHA) is a potent anti-cancer drug that has limited clinical applications due to poor water solubility and low bioavailability. We designed a biodegradable poly(ethylene glycol) methyl ether-poly(ε-caprolactone) (MPEG-PCL) micelle carrier for DHA using the self-assembly method. The DHA/MPEG-PCL nanoparticles were spherical with an average particle size of 30.28 ± 0.27 nm, and released the drug in a sustained manner in aqueous solution. The drug-loaded nanoparticles showed dose-dependent toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…5,6 Increasing evidence has shown that DHA can inhibit the growth of various cancers, including breast cancer, pancreatic ductal adenocarcinoma, hepatocellular carcinoma, CC, and cervical cancer. [7][8][9][10][11] The role of DHA in regulating tumorigenesis is being increasingly appreciated as its preferential antiproliferative effects on cancer versus normal cells have been revealed. 12 In this study, we found that DHA not only inhibited CC cell proliferation but also synergistically enhanced the cytotoxicity of oxaliplatin in CC cells.…”
Section: According To the Latest Version Of The National Comprehensivementioning
confidence: 99%
See 1 more Smart Citation
“…5,6 Increasing evidence has shown that DHA can inhibit the growth of various cancers, including breast cancer, pancreatic ductal adenocarcinoma, hepatocellular carcinoma, CC, and cervical cancer. [7][8][9][10][11] The role of DHA in regulating tumorigenesis is being increasingly appreciated as its preferential antiproliferative effects on cancer versus normal cells have been revealed. 12 In this study, we found that DHA not only inhibited CC cell proliferation but also synergistically enhanced the cytotoxicity of oxaliplatin in CC cells.…”
Section: According To the Latest Version Of The National Comprehensivementioning
confidence: 99%
“…Dihydroartemisinin (DHA), a derivative of ART, is the active metabolite of ART compounds and has been reported to exhibit strong antiviral, antibacterial, and anticancer activities 5,6 . Increasing evidence has shown that DHA can inhibit the growth of various cancers, including breast cancer, pancreatic ductal adenocarcinoma, hepatocellular carcinoma, CC, and cervical cancer 7–11 . The role of DHA in regulating tumorigenesis is being increasingly appreciated as its preferential antiproliferative effects on cancer versus normal cells have been revealed 12 …”
Section: Introductionmentioning
confidence: 99%
“…In many cases, more than one type of polymer can be contained in a DHA-encapsulated system. For instance, DHA-phospholipid complex NPs coated with biodegradable poly(lactic-co-glycolic acid) (PLGA) [103] or PEG methyl ether-poly(e-caprolactone) (MPEG-PCL) DHA polymeric micelles [104] were prepared to prevent drugs from rapid blood/renal clearance and suppress premature burst release. When compared with the unformulated drug, the polymeric NPs significantly enhanced the cytotoxicity of DHA.…”
Section: Nanoscale Drug Delivery Of Dihydroartemisininmentioning
confidence: 99%
“… DHA formulation Cancer Type Animal model Dosage Route Safety issues Ref. Tf-8arm-PEG-DHA NPs Lewis lung carcinoma LLC tumor-bearing female C57BL/6 mice 5 mg/kg or 10 mg/kg DHA every 2 d IV injection Reduced hypersensitivity reactions; no severe hematotoxicity [101] DHA-PEG-PTX nanosystems Colorectal cancer HT-29 tumor-bearing Balb/c nude mice 5 mg/kg PTX and 10 mg/kg DHA every 3 d IV injection No significant body weight loss [102] DHA/MPEG-PCL NPs Cervical cancer HeLa tumor-bearing female athymic BALB/C nude mice 20 mg/kg DHA every 2 d IV injection No significant pathological changes, weight loss or inflammatory lesions [104] DOX and DHA coencapsulated Soluplus®-TPGS mixed micelles Breast cancer MCF-7 xenografted female BALB/c nude mice 15 mg/kg DHA and/or 15 mg/kg DOX every 2 d IV injection Reduced the cardiotoxicity; avoided hepatic damage and necrosis [105] OxPt/DHA core-shell particles Colorectal cancer CT26 or MC38 tumor-bearing BALB/c, C57Bl/6 wild-type or Rag 2−/− mice 8 mg/kg OxPt, 2.86 mg/kg DHA, and/or 75 µg PD-L1 antibody every 3 d IP injection Reduced peripheral neuropathy [106] R 8 modified epirubicin–DHA liposomes Non-small-cell lung cancer A549 tumor-bearing BALB/c nude mice 3 mg/kg epirubicin; (epirubicin/DHA= 1:5, molar ratio) every 2 d IV injection Neglected systemic toxicity [116] LDLR-targeted lipid NPs coloading sorafenib and DHA Hepatocellular carcinoma HepG2 tumor-bearing BALB/c nu/nu nude mice 5 mg/kg SRF and/or DHA every 3 d IV injection Reduced body weight loss as compared to free drugs [118] Alkyl glycoside-modified DHA liposomes Hepatocellular carcinoma H22 tumo...…”
Section: Challenges In Clinical Applicationmentioning
confidence: 99%
“…Sibusiso et al have reported the nanosystem doped with artemisinins, including polymeric, metal-based, and lipid nanoparticles, against cancer by enhancing effects recuperating poor solubility and bioavailability and targeting delivery ( Alven and Aderibigbe, 2020 ). Concurrently, Yun et al depicted a biodegradable poly (ethylene glycol) methyl ether-poly (ε-caprolactone) (MPEG-PCL) loading dihydroartemisinin (DHA) had allowed for a stronger anti-angiogenic effect than free DHA ( Lu et al, 2020 ).…”
Section: Pharmaceutical Delivery Systems Against Tumor Angiogenesismentioning
confidence: 99%